2023
DOI: 10.3390/w15122242
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Subsurface Drip Irrigation Schedule of Alfalfa in Northwest China

Abstract: Determination of an optimum irrigation amount and buried depth of subsurface drip irrigation laterals is significantly important in improving crop yield and irrigation water using efficiency in arid regions. In this study, the effects of three irrigation volumes (15.0, 22.5 and 30.0 mm) and three burial depths (10, 20 and 30 cm) of drip laterals on water consumption, yield and water productivity of alfalfa were investigated in a field trial. The water balance equation and FAO-56 crop coefficient methods were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Under the considerations of purple alfalfa’s growth requirements, efficient water resource use, and economic profitability, it was advisable to ensure initial soil moisture levels between 0.8 θ fc and 1.0 θ fc before regreening, with an optimal irrigation quota of 30 mm for subsequent growth phases. Zheng et al’s [ 11 ] research suggested an optimized irrigation amount of 22.5 to 30.0 mm per event, with events occurring every 5 to 7 days for alfalfa in their study area. Our study results were consistent with Zheng’s findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the considerations of purple alfalfa’s growth requirements, efficient water resource use, and economic profitability, it was advisable to ensure initial soil moisture levels between 0.8 θ fc and 1.0 θ fc before regreening, with an optimal irrigation quota of 30 mm for subsequent growth phases. Zheng et al’s [ 11 ] research suggested an optimized irrigation amount of 22.5 to 30.0 mm per event, with events occurring every 5 to 7 days for alfalfa in their study area. Our study results were consistent with Zheng’s findings.…”
Section: Discussionmentioning
confidence: 99%
“…It markedly improved soil moisture profiles, boosted alfalfa yields, and enhanced the overall efficiency of water use in irrigation practices. Zheng et al [ 11 ] employed a water balance approach and FAO-56 guidelines to ascertain the evapotranspiration rates and the optimal amount and depth of subsurface drip irrigation, concluding values of 22.5–30.0 mm and 20 cm, respectively. In a similar quest, Wang Xing et al [ 12 ] utilized a two-factor split-plot design to determine the ideal irrigation and fertilization rates for alfalfa seed production in Ningxia’s drip-irrigated fields.…”
Section: Introductionmentioning
confidence: 99%
“…The depth of burial of the drip tape has an important effect on yield and water savings with subsurface drip irrigation. A burial depth of 20 cm has been recommended for alfalfa in northwestern China (Zheng et al, 2023). For spring maize, 30 cm of drip irrigation laterals in silty clay soils is considered bene cial (Guo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However, the lm residue causes white pollution, damages the soil structure, and destroys the normal growth and development of seedlings, which is not conducive to the sustainable development of potato production. Subsurface drip irrigation, in which drip tape is buried in the eld soil, has been shown to be a novel means of conserving water resources and improving water use e ciency for some crops (Yao et al, 2021;Zheng et al, 2023). Compared with the surface irrigation mode, the soil covered with drip tape reduced the ineffective evaporation from the surface and saved water, and showed a similar effect with mulch lm covering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation